Interprofessional Education in Health and Dental Hygiene Fields in Korea: A Scoping Review - Eun-Mi Choi; Su-Kyung Park (치위생과학회지)
Background: Interprofessional education (IPE) is a critical strategy for fostering collaboration in healthcare. As the role of dental hygienists expands beyond clinical support to include community-based and preventive care, the integration of IPE into dental hygiene education has gained increasing attention. However, evidence regarding the role of dental hygiene in Korean IPE programs is limited. Methods: This scoping review followed the Arksey and O’Malley framework. Four databases (Google Scholar, RISS, KISS, and DBpia) were searched for Korean-language articles published between 2010 and 2025. In total, 246 articles were identified. After removing duplicates and screening titles and abstracts, 42 articles were selected for full-text review. Ultimately, 23 studies met the inclusion criteria and were analyzed using a structured framework covering publication data, study design, program characteristics, and educational outcomes. Results: Most IPE programs adopted short- to mid-term interventions (1 day to 15 weeks) using team-based learning, simulations, and scenario-based education. Positive outcomes included improved interprofessional attitudes, communication skills, and professional identity. Studies on dental hygiene-related IPE emphasized community-based care, prevention, and oral health in the elderly population. However, the key challenges included unequal academic levels among students, scheduling and space conflicts, limited faculty preparation, and a lack of standardized evaluation tools. Few studies focused on dental hygiene as a central discipline, highlighting the need for its increased integration. Conclusion: IPE participation in dental hygiene education in Korea remains limited but has the potential to enhance collaboration, professional identity, and patient-centered care. To advance IPE integration, flexible curricula, institutional support, faculty training, and clear role recognition for dental hygienists are needed. These findings provide foundational evidence for guiding curriculum development and policy improvements in health education.